Two new species of Anthurium Schott (Araceae) from the Atlantic Forest in Minas Gerais, Brazil - Hammes, Janaine K. [UNESP]; Coelho, Marcus A. N.; Temponi, Livia G.; Lombardi, Julio Antonio [UNESP] (Magnolia Press, 2020)
Two new species of the genus Anthurium are described from the Serra do Brigadeiro State Park, in the Atlantic Forest region, southeastern Brazil. Anthurium atrovinosum was found from 1450 to 1720 m and A. brigadeiroense from 1260 to 1650 m. Although they are sympatric species, A. atrovinosum reaches higher elevations, while A. brigadeiroense can be found up to 1650 m. Both belong to Anthurium sect. Urospadix subsect. Insculptinervia, but are easily differentiated by the leaf blade shape, fruit color. Descriptions, illustrations, photographs, comments on geographical distribution, ecology, phenology and comparisons with other similar species are presented.
Keywords: Anthurium atrovinosum; Anthurium brigadeiroense; Anthurium sect. Urospadix subsect. Insculptinervia